Systemic Risk Transmission from the United States to Asian Economies During the COVID-19 Period. (March 2023) - Narayan, Shivani; Kumar, Dilip
The study investigates the systemic risk transmission from the US banking sector and the US market to the five most economically impacted Asian nations (Thailand, Malaysia, the Philippines, India, and Singapore) during the COVID-19 period of 2020. We consider the conditional value-at-risk (CoVaR) approach to estimate the systemic risk of the given economies at 5% quantile (for severe downturn risk) and 20% quantile (for moderate downturn risk). Our findings demonstrate a rise in systemic risk for these Asian countries in 2020, particularly in the first half of the year. The findings also provide evidence of the significant systemic risk transmission from the US banking sector and the US stock market to the majority of the given Asian economies at both quantiles. The study further highlights the significant contribution of the US financial market in increasing the systemic risk of the given Asian economies in 2020. We find similar results for systemic risk transmission from the UK, the European Union, and Japan to the given Asian economies. The findings have implications for market participants, risk managers, and regulators who are concerned with risk diversification and tracking the routes of risk shock transmission. JEL Codes: G10; G18; G20